2016
DOI: 10.4269/ajtmh.15-0377
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene Practices During Food Preparation in Rural Bangladesh: Opportunities to Improve the Impact of Handwashing Interventions

Abstract: Abstract. This study explored the steps of food preparation, related handwashing opportunities, current practices, and community perceptions regarding foods at high-risk of contamination such as mashed foods and salads. In three rural Bangladeshi villages, we collected qualitative and observational data. Food preparation was a complex and multistep process. Food preparation was interrupted by tasks that could contaminate the preparers' hands, after which they continued food preparation without washing hands. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…The CDC estimates that nearly half of all food-borne illnesses in the United States [57] are caused by contaminated fresh produce and that more than 30% of gastroenteritis cases in low-and middle-income countries are linked to food borne transmission [58]. Risk factors for food contamination in the low-and middle-income settings are different than high-income countries because cooked food is more common and is usually freshly prepared in households [29,59]. The causes of the fecal contamination detected on the produce in this study are not known and may be due to poor agricultural practices by farmers (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CDC estimates that nearly half of all food-borne illnesses in the United States [57] are caused by contaminated fresh produce and that more than 30% of gastroenteritis cases in low-and middle-income countries are linked to food borne transmission [58]. Risk factors for food contamination in the low-and middle-income settings are different than high-income countries because cooked food is more common and is usually freshly prepared in households [29,59]. The causes of the fecal contamination detected on the produce in this study are not known and may be due to poor agricultural practices by farmers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies in rural Bangladesh identified that produce washing practices during salad preparation (uncooked and mashed cucumber, tomato etc.) within low-income neighborhoods were inadequate, and salads were often contaminated due to poor hygiene practices [29,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when only the right hand was used by the food preparer, the hand would be contaminated due to other interrupting events (toileting, adding cow dung fuel to the fire, etc.) which may not be followed by handwashing before going back to food preparation . If washing both hands is required in order for an observed behaviour to be considered as handwashing, the prevalence of handwashing with water would be reduced to 6.9%, and prevalence of handwashing with soap would be reduced to 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Our key informants included the key personnel from the Dhaka University team who are responsible to oversee the MAR implementation in the field. IDI interview and FGD sample sizes were determined from data saturation attainment in previous water, sanitation and hygiene qualitative studies [21][22][23]. [24].…”
Section: Introductionmentioning
confidence: 99%